Insects found in birds’ nests from Argentina: Coryphistera alaudina Burmeister, 1860 (Aves: Furnariidae), their inquiline birds and mammals, new hosts for Psammolestes coreodes Bergroth, 1911 and Triatoma platensis Neiva, 1913 (Hemiptera: Reduviidae: Triatominae) - Turienzo, Paola; Di Iorio, Osvaldo (Zootaxa, 2014)
The insect fauna in nests of Coryphistera alaudina Burmeister, 1860 (Aves: Furnariidae) were studied in the provinces of Santiago del Estero, Chaco, Córdoba, and La Pampa in Argentina. A total of 7364 insect specimens comprising 77 taxa in a total of 29 families and 7 orders was found in their nests: 40 identified to species, 23 identified to genus, and 14 identified to family. Coryphistera alaudina and some of their vertebrate inquilines are new host records for the triatomine bugs Psammolestes coreodes Bergroth, 1911 and/or Triatoma platensis Neiva, 1913 (Hemiptera: Reduviidae). The insects in the nests of C. alaudina are separated by functional guilds, and their permanence time inside the nests are presented in a new manner and discussed.